Maresin1 Protect Against Ferroptosis-Induced Liver Injury Through ROS Inhibition and Nrf2/HO-1/GPX4 Activation - Yang, Wenchang; Wang, Yaxin; Zhang, Chenggang; Huang, Yongzhou; Yu, Jiaxian; Shi, Liang; Zhang, Peng; Yin, Yuping; Li, Ruidong; Tao, Kaixiong (Frontiers in Pharmacology, 2022)
Drugs, viruses, and chemical poisons stimulating live in a short period of time can cause acute liver injury (ALI). ALI can further develop into serious liver diseases such as cirrhosis and liver cancer. Therefore, how to effectively prevent and treat ALI has become the focus of research. Numerous studies have reported Maresin1 (MaR1) has anti-inflammatory effect and protective functions on organs. In the present study, we used D-galactosamine/lipopolysaccharide (D-GalN/LPS) to establish an ALI model, explored the mechanism of liver cells death caused by D-GalN/LPS, and determined the effect of MaR1 on D-GalN/LPS-induced ALI. In vivo experiments, we found that MaR1 and ferrostatin-1 significantly alleviated D-GalN/LPS-induced ALI, reduced serum alanine transaminase and aspartate transaminase levels, and improved the survival rate of mice. Meanwhile, MaR1 inhibited hepatocyte death, inhibited tissue reactive oxygen species (ROS) expression, reduced malondialdehyde (MDA), reduced glutathione (GSH), GSH/oxidized glutathione (GSSG), and iron content induced by D-GalN/LPS in mice. In addition, MaR1 inhibited ferroptosis-induced liver injury through inhibiting the release of interleukin-1β (IL-1β), tumor necrosis factor-α (TNF-α), and IL-6. Subsequently, western blot showed that MaR1 improved the expression of nuclear factor E2-related factor 2(Nrf2)/ heme oxygenase-1 (HO-1)/ glutathione peroxidase 4 (GPX4). In vitro experiments, we found that MaR1 inhibited LPS-induced and erastin-induced cell viability reduction. Meanwhile, we found that MaR1 increased the MDA and GSH levels in cells. Western blot showed that MaR1 increased the expression level of Nrf2/HO-1/GPX4. Next, the Nrf2 was knocked down in HepG2 cells, and the results showed that the protective effect of MaR1 significantly decrease. Finally, flow cytometry revealed that MaR1 inhibited ROS production and apoptosis. Overall, our study showed MaR1 inhibited ferroptosis-induced liver injury by inhibiting ROS production and Nrf2/HO-1/GPX4 activation.